2022
DOI: 10.1186/s12879-022-07364-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors on healthcare-associated infections among tuberculosis hospitalized patients in China from 2001 to 2020: a systematic review and meta-analysis

Abstract: Background China has been still suffering from high burden attributable to tuberculosis (TB) and healthcare-associated infections (HAIs). TB patients are at high risk to get HAIs. Evidence-based guidelines or regulations to constrain the rising HAIs among TB hospitalized patients are needed in China. The aim of this systematic review and meta-analysis is to investigate the risk factors associated with HAIs among TB hospitalized patients in Chinese hospitals. Metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…1) Our research team has conducted a systematic review and meta-analysis to identify risk factors associated with HAIs among TB hospitalized patients in China. The study concluded a list of signi cant risk factors, including age older than 60 years, presence of complications, diabetes mellitus, invasive procedure, longer than 15 hospitalization days, secondary TB, smoking, presence of underlying disease, and use of antibiotics (9). Considering the data availability from this TB hospital, gender, age older than 60 years, diabetes mellitus, invasive procedure, more than 15 hospitalization days, presence of underlying disease, and used of antibiotics were selected as potential risk factors in this case study.…”
Section: Framework Developmentmentioning
confidence: 99%
“…1) Our research team has conducted a systematic review and meta-analysis to identify risk factors associated with HAIs among TB hospitalized patients in China. The study concluded a list of signi cant risk factors, including age older than 60 years, presence of complications, diabetes mellitus, invasive procedure, longer than 15 hospitalization days, secondary TB, smoking, presence of underlying disease, and use of antibiotics (9). Considering the data availability from this TB hospital, gender, age older than 60 years, diabetes mellitus, invasive procedure, more than 15 hospitalization days, presence of underlying disease, and used of antibiotics were selected as potential risk factors in this case study.…”
Section: Framework Developmentmentioning
confidence: 99%